THE EFFECTIVENESS OF ELECTRONIC-BASED VILLAGE FINANCIAL MANAGEMENT THROUGH SISKEUDES IN DUKUH TENGAH VILLAGE, BUDURAN DISTRICT - Difayanti, Erlidha Catur; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the effectiveness of the Village Financial System application (SISKEUDES) in supporting financial management within Dukuh Tengah Village, Buduran District, focusing on system quality, information quality, service quality, and user satisfaction. Method: A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation to capture the practical implementation of SISKEUDES. Results: The findings reveal that SISKEUDES has improved the efficiency of financial reporting, enhanced accessibility to financial information, and strengthened transparency in budget management. Despite these advantages, challenges remain in the form of limited training for operators, technical constraints, and low public understanding of the financial information produced by the system. Novelty: This study contributes to the discourse on village governance by providing an in-depth evaluation of SISKEUDES through multiple quality dimensions, offering insights into both its benefits and limitations, and highlighting the importance of capacity building and infrastructure development to maximize the system’s role in ensuring accountable and transparent village financial management.